Monitoring of Technical Condition of Buildings by Seismic Method - Alena A. Kurdanova; Mikhail N. Voskresenskiy; Elena A. Kosorotova; Gennadiy I. Parygin (Structural Mechanics of Engineering Constructions and Buildings)
The research object is the natural resonance frequencies of the buildings of the Ural Branch of the Russian Academy of Sciences (UB RAS) located in Ekaterinburg and their distribution at observation points. The method of spectral ratios (HVSR or the Nakamura method), which allows hidden construction defects to be identified, is applied to analyze the resonance characteristics. Periodic monitoring of technical condition allows to calculate and evaluate changes in dynamic characteristics over time. Equal values of the amplitude extrema of the spectral ratio curve and uniform distribution of the values throughout the building indicate a normal operational state of the structure. The presence of abnormally high values at some points may be due to hidden defects and requires additional study. A method for calculating vulnerability coefficient is demonstrated. According to the results of annual monitoring (since 2017), the stable state of the Institute of Geophysics building of UB RAS is demonstrated, and a comparison with resonant frequencies obtained from the standard project (Institute of Geology Geochemistry of UB RAS) is presented. This article presents a method for assessing seismic stability by calculating horizontal acceleration ( ) at observation points. Acceleration is calculated at the maximum possible seismic event in the studied region (44 cm/s²). The possible maximum acceleration is calculated, taking into account the characteristics of the soil, for the observation point with the highest , = 30.6 cm/s², which corresponds to an earthquake intensity of 5.6.